Incest as a rhetorical device: The shock effect of the allegory in Ezekiel 16 - Kugler, Gili (Scottish journal of theology, 2024)
Ezekiel 16 paints one of the harshest pictures in the Hebrew Bible. In a brokenhearted cry of rage, the prophet contemplates Jerusalem's history of relationship with God. Employing familial imagery, the relationship is characterised by constraints and penalties, including instances of sexual violence imposed by God. Consequently, the allegory challenges the perception of the deity as an exemplary figure. This article posits that the allegory deliberately delivers a jolt to its recipients by depicting God as transgressing a social taboo, by altering his role for the people from a father to a spouse. This depiction of incestuous relationship wields the power to evoke threat and terror. It acknowledges that the breaching of the taboo of a father-daughter incestuous relationship, albeit inadvisable, is possible. By ascribing to God a behaviour that fathers strive to avoid, the reproach captures the imagination of its recipients, leaving a profound impact upon them.